American snout, Libytheana carinenta (Cramer) (Insecta: Lepidoptera: Nymphalidae: Libytheinae) - Donald W. Hall; Jerry F. Butler (EDIS, 2009)
EENY-452, a 4-page illustrated fact sheet by Donald W. Hall and Jerry F. Butler, is part of the Featured Creatures collection. It describes this small, dull colored butterfly with an elongated snout — its distribution, description, life cycle and biology, and hosts. Includes references. Published by the UF Department of Entomology and Nematology, June 2009. 2009 version unavailable, September 2014 revision included instead.